The strategy of personalization: the debates of 2015 and 2016 elections in Spain - Zamora Medina, Rocío; Rebolledo, Marta (Estudios sobre el Mensaje Periodístico, 2019)
In this article, we make an empirical analysis on the communicative construction of the discourse of the candidates for the Spanish presidency participating in electoral debates of 2015 and 2016 focusing on the use of personalization as a political strategy. From an evolutionary approach, the study reveals the personalization of discourse is a characteristic becoming generalized within the electoral debates of Spain, especially among the candidates from new parties compared to those from traditional parties. However, it can be inferred from the analysis that personalization, although includes more visibility of the candidate comparing to the party and also a salience of personal features linked to his own personality, does not reach aspects of the candidates’ private lives.